Improving management in India - Bloom, Nick; Eifert, Benn; Mahajan, Aprajit; McKenzie, David; Roberts, John (World Bank, Washington, DC, 2012)
The tenth in series of impact notes profiles early results from an ongoing randomized experiment, which is the first such experiment with large firms. Early results show how much difference improving management practices can make. Recent measurement has found that the majority of firms in developing countries are poorly managed by global standards. This is the case in India, where, apart from multinationals, most firms do not collect and analyze data systematically in their factories, tend to use less effective target-setting and monitoring, and employ inefficient promotion and reward systems. While there is a positive correlation between better management practices and higher productivity, it is not clear whether this reflects a causal relationship or just the influence of other unobserved differences across firms.